Elbląskie inicjatywy antysystemowe w pierwszym roku stanu wojennego (13 grudnia 1981 – 12 stycznia 1983 roku) - Nawrocki, Karol (Pamięć i Sprawiedliwość, 2011)
This article describes “Solidarity” circle of Elbląg, which after 13 December 1981 faced the necessity of changing hitherto methods of its activity. Since that time the most crucial assignment to be fulfilled by former members of the “Solidarity” movement (split after the introduction of martial law) was sustaining the idea of “Solidarity” through distribution of illegal publications and organizing patriotic demonstrations.An initial section of this article is a paragraph concerning “Solidarity” of Elbląg at the time of its legal activity. It focuses on the August 1980s events in Elbląg and on the scale of the public support for the “Solidarity” before the introduction of martial law. The main part of the text concentrates both on spontaneous, antiregime initiatives of the youth of Elbląg (Independent Poland Movement [Ruch Polski Niepodległej, RPN], Kalinscy brothers) and on coordinated actions of the first underground Edmund Krasowski’s group, taken after 13 December 1981. A large piece of the text refers to two patriotic demonstrations in Elbląg on 18December 1981 and between 3 and 5 May 1982. The May manifestations are considered to have been the biggest social protest in Elbląg in the 1980s.Major initiatives with subsequent activities of the Elbląg underground are compared in the ending to this article. This comparison enabled to advance the thesis that all activities presented in this article were the best organized and particularly intense throughout the period after 13 December 1981 in Elbląg.This article is based on documents from the Institute of National Remembrance’s Archive in Gdańsk and from the State Archive in Łódź with the headquarters in Malbork. Numerous testimonies of witnesses such as Antoni Borowski, Edmund Krasowski, Waldemar Matejak as well as various publications on this topic were used as a complement to those archival documents. The article is an important step in historical research on the underground activity of “Solidarity” and other opposition groups of Elbląg in the 1980s.